2021
DOI: 10.3389/fonc.2021.633833
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body MRI vs. PET/CT for the Detection of Bone Metastases in Patients With Prostate Cancer: A Systematic Review and Meta-Analysis

Abstract: Purpose: A recent meta-analysis in patients with non-small cell lung cancer showed no difference between whole-body magnetic resonance imaging (WBMRI) and positron emission tomography/computed tomography (PET/CT), but no such study is available for prostate cancer (PCa). This study aimed to compare WBMRI and PET/CT for bone metastasis detection in patients with PCa.Materials and Methods: PubMed, Embase, and the Cochrane library were searched for papers published up to April 2020. The population was the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
1
6
1
Order By: Relevance
“…Our study thus confirms the high diagnostic performance of WB-MRI for bone lesions detection that was primarily demonstrated in comparison with conventional techniques [ 22 , 29 , 30 , 31 ]. This study, however, suggests that PSMA PET-CT reaches similar diagnostic accuracy for bone metastasis detection, in line with published comparisons between MRI and PET/CT using either choline or PSMA ligands [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 89%
“…Our study thus confirms the high diagnostic performance of WB-MRI for bone lesions detection that was primarily demonstrated in comparison with conventional techniques [ 22 , 29 , 30 , 31 ]. This study, however, suggests that PSMA PET-CT reaches similar diagnostic accuracy for bone metastasis detection, in line with published comparisons between MRI and PET/CT using either choline or PSMA ligands [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 89%
“…There are studies showing that whole-body MRI has high sensitivity (80–94%) and specificity (83–94%) in demonstrating bone metastases in PCa patients [5,9,23,24]. In our study, the sensitivity was slightly lower than the previous studies (75%), while the specificity was observed at similar levels (96%).…”
Section: Resultscontrasting
confidence: 77%
“…The benefits of whole-body MRI in assessing skeletal metastases in various cancer types are well documented, with most reports suggesting the superiority of whole-body MRI over bone scintigraphy, whereas whole-body MRI and 18 F-FDG PET-CT showed a comparable diagnostic performance. [23][24][25][26][27][28] However, a few studies mainly investigated the benefits of whole-body MRI in identifying metastases in bone sarcomas. For example, in their subset of patients with Ewing sarcoma (n = 20) and osteosarcoma (n = 3), Daldrup-Link et al 29 documented that whole-body MRI had a sensitivity of 80% in identifying skeletal metastases, which was on par with 99mTc-MDP bone scintigraphy but lower than PET.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of whole-body MRI in assessing skeletal metastases in various cancer types are well documented, with most reports suggesting the superiority of whole-body MRI over bone scintigraphy, whereas whole-body MRI and 18 F-FDG PET-CT showed a comparable diagnostic performance 23–28 . However, a few studies mainly investigated the benefits of whole-body MRI in identifying metastases in bone sarcomas.…”
Section: Discussionmentioning
confidence: 99%